The Influence of Self-efficacy on Self-Anxiety Based on Students' Mathematics Learning - Ningsih, Nur Indah Septia; Maharani, Sri; Shofari, Mia Rahma; Verlanda, Mohamad Abif; Riyanto, Onwardono Rit (Journal of Mathematics Instruction, Social Research and Opinion, 2023)
Anxiety towards a particular subject is experienced by most students in various schools, especially in mathematics. This research aims to determine the influence of self-efficacy and self-anxiety on mathematics in one of the schools in Cirebon City. The sample was selected using a purposive sampling technique, with a sample size of 40 students, each representing a higher grade. This study employs a quantitative approach. The data analysis techniques used are regression analysis and ANOVA test. The results of the research conclude that self-efficacy does not have a significant influence on self-anxiety in mathematics. Based on the R-Square analysis, a coefficient of determination of 0.238 is obtained, indicating that self-efficacy accounts for 28.5% of the influence on self-anxiety, while other variables influence the remaining 71.5%. Meanwhile, the ANOVA analysis shows a value of ÿ1 of 0.232. This means that each unit increase in the coefficient of self-efficacy will influence 0.232 on self-anxiety. Additionally, ÿ is equals 45.146, which means that if self-efficacy (d) is equal to 0, self-anxiety will be equal to 15.382. Therefore, it can be concluded that self-efficacy does not have a significant influence on self-anxiety in students, particularly in the subject of mathematics.